Pengaruh Penghargaan Finansial, Pengetahuan Persyaratan Akuntan Publik Dan Lingkungan Keluarga Terhadap Minat Mahasiswa Akuntansi Dalam Pemilihan Karir Sebagai Akuntan Publik - Ni Kadek Ade Riski Sapitri; Cokorda Gde Bayu Putra; Ni Putu Yeni Yuliantari (Hita Akuntansi dan Keuangan, 2023)
Public accountants play a crucial part in society's decision-making processes. However, the number of accounting graduates in Indonesia is significantly lower than the number of practicing accountants. This suggests that public accounting is not yet a popular career choice amongst students. This research set out to answer the question, "Do financial incentives, familiarity with profession-specific requirements, and personal circumstances influence accounting students' interest in becoming public accountants?" Denpasar college accounting majors in the year 2019 were the subjects of this research. Proportional stratified random sampling. There were 95 people in the sample. The use of a questionnaire to gather information. Here, we analyzed the data with several different statistical methods, including multiple linear regression, the coefficient of determination, a F test, and a t test. Financial incentives, prior knowledge of public accountant requirements, and encouraging family environments all had a positive and significant effect on accounting students' interest in pursuing a career in public accounting.